Periodic wave analysis to the time-fractional phi-four and (2+1) dimensional CBS equations - Nahar Ananna, Samsun; Al – Mamun, Abdulla; An, Tianqing (International Journal of Physical Research, 2021)
In this paper, we investigate some innovative and exact travelling wave solutions to the time-fractional phi-four equation and the (2+1) dimensional Calogero-Bogoyavlanskil schilf (CBS) equation using the ( )-expansion method. Periodic solutions are displayed in hyperbolic, trigonometric, and rational function solutions. Subsequently, we construct some new solutions connecting the free parameters of the phi-four equation and the CBS equation, which are characterized into three complete forms: rational function, trigonometric function, and hyperbolic functions. Graphical representations of some attained solutions are also presented in this article. Hence, this study shows the efficiency and the easiness of the ( )-expansion technique with the assistance of emblematically computational software MATLAB and Mathematica.Â Â